2017
DOI: 10.1039/c6md00458j
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent ligands for the serotonin 5-HT4 receptor

Abstract: 5-HT receptors are known to form constitutive dimers in membranes. To explore whether multivalency can enhance ligand interactions and/or efficacy in 5-HT receptors, the structure of the partial agonist ML10302 was modified with oligo(ethylene glycol) chains, thus generating, by a gradual approach, short and long tethered bivalent or tetravalent ligands and the corresponding spanner-linked monovalent controls. Both bivalent and tetravalent ligands displayed a 10-20-fold increase in binding affinity compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…In agreement with the results obtained with the previously published quinoline derivatives 7a and b, 16 amide 7c, was found to be virtually inactive, whereas the corresponding ester 7d showed an inhibition constant value in the nanomolar range. Thus, the replacement of BM-1 of ester 7a with BM-2 as in ester 7d produced a negligible effect on the binding affinity, which could be further modulated by the presence of the substituents in position 4 of the piperidine moiety as in ester derivatives 7e and f. In particular, the introduction of a -CH 2 OH group (as in 7e) was well tolerated by the receptor binding site, whereas the presence of Boc-amino as in 7f produced a significant decrease in the affinity.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with the results obtained with the previously published quinoline derivatives 7a and b, 16 amide 7c, was found to be virtually inactive, whereas the corresponding ester 7d showed an inhibition constant value in the nanomolar range. Thus, the replacement of BM-1 of ester 7a with BM-2 as in ester 7d produced a negligible effect on the binding affinity, which could be further modulated by the presence of the substituents in position 4 of the piperidine moiety as in ester derivatives 7e and f. In particular, the introduction of a -CH 2 OH group (as in 7e) was well tolerated by the receptor binding site, whereas the presence of Boc-amino as in 7f produced a significant decrease in the affinity.…”
Section: Resultssupporting
confidence: 92%
“…7 For instance, the partial 5-HT 4 R agonist PRX-03140 (3) by Epix Pharmaceuticals was reported to improve cognitive processes by increasing the release of acetylcholine and soluble amyloid precursor protein (sAPPα). 7 In the context of our interest in developing new serotonin receptor ligands, [9][10][11][12][13][14][15][16] the aromatic moieties (AM) of standard 5-HT 4 R ligands 3 and 5 were replaced with the 2-methoxyquinoline system to obtain flexible compounds 7a and b (Fig. 2), which were in turn transformed into the corresponding conformationally constrained derivatives 8a-g in the aim of obtaining information on their interaction with the 5-HT 4 R. 16 Very interestingly, ester 7a showed a 5-HT 4 R affinity in the nanomolar range along with antagonist properties, and the structure-activity relationship analysis in the conformationally constrained derivatives 8a-g suggested that the nature and the position of the substituents played a crucial role in determining the interaction with their receptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These efforts were quickly driven forward by Halazy et al to expand the use of bivalent molecules in the study of the serotonergic system developing a vast array of high affinity selective ligands. Since then, evidence of oligomerization among the 5-HT receptors has become increasingly available leading to efforts toward discovering novel bivalent ligands with increased subtype selectivity capable of discriminating among receptor subtypes. Likewise, bivalent ligands have also played a prominent role in the study of cannabinoid receptors (CB1/2). Starting with the efforts of Zhang et al, a large library of bivalent ligands have been developed to study homo- and heteromers formed by the cannabinoid receptors. Despite remaining unclear whether current bivalent ligands of the cannabinoid receptor system do indeed simultaneously bind two receptors within a dimer as postulated, bivalent ligands remain attractive tools in the study of these receptor complexes. …”
Section: Bivalent Molecules For Other Gpcrs To Study Homomers and Het...mentioning
confidence: 99%
“…The request of new dendrimeric structures is continuously increasing given their large application in biomedical field, but also as materials for catalytic processes and composite materials 4,5 . Among these, poly(propylene imine) (PPI) and poly(amidoamine) (PAMAM) dendrimers represent two outstanding constructs that have been extensively investigated from the point of view of their potential applications as drug and gene carriers 3,6–13 . These dendrimers are characterized by terminal amino groups generating a positively charged surface, which represents the portion most exposed to the external environment.…”
Section: Introductionmentioning
confidence: 99%